2012
DOI: 10.1128/jb.06330-11
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Targeting, Ultrastructure, and Single Molecule Localization of the Enteropathogenic Escherichia coli Type IV Pilus Secretin BfpB

Abstract: Type IV pili (T4P) are filamentous surface appendages required for tissue adherence, motility, aggregation, and transformation in a wide array of bacteria and archaea. The bundle-forming pilus (BFP) of enteropathogenic Escherichia coli (EPEC) is a prototypical T4P and confirmed virulence factor. T4P fibers are assembled by a complex biogenesis machine that extrudes pili through an outer membrane (OM) pore formed by the secretin protein. Secretins constitute a superfamily of proteins that assemble into multimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 84 publications
3
25
0
Order By: Relevance
“…Prior to our study, the working paradigm for secretin structure has been that secretin monomers assemble under C 12 symmetry to construct the dodecameric rings as visualized by electron microscopy (11,15,37). In contrast, our study supports a hexameric assembly of dimers, a model that was also recently suggested by other studies (17,18).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Prior to our study, the working paradigm for secretin structure has been that secretin monomers assemble under C 12 symmetry to construct the dodecameric rings as visualized by electron microscopy (11,15,37). In contrast, our study supports a hexameric assembly of dimers, a model that was also recently suggested by other studies (17,18).…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, negative stain EM images of pseudocrystals of XcpQ from Pseudomonas alcaligenes (11) clearly show hexagonal particles, consistent with our proposed model. In addition, a recent study by EM of the structure of BfpB, the secretin for type IV pili, proposed a dodecameric secretin that can be assembled as a set of six dimers (17). Finally, we note that the crystal structure of the periplasmic domain of EscC, the T3SS secretin from enteropathogenic E. coli, also forms dimers in the crystal lattice (16), but the possible relevance of dimers in the oligomeric assembly of T3SS with an even number of subunits has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Alternatively, data from the T2SS suggests that the secretin is assembled as a hexamer of dimers (40)(41)(42); in this case, the arrangement may be one PilMNOP complex for every two PilQ monomers (1:1:1:1:2 stoichiometry). Differences in orientation of the N0 domain of PilQ in a dimer versus monomer configuration might explain why we saw differences in PilPQ interactions when fragments versus full periplasmic domains of PilQ were used for pulldowns.…”
Section: Discussionmentioning
confidence: 99%
“…The BfpB secretin of an Escherichia coli T4PS is also a lipoprotein, but lipid modification is not required for targeting to the OM (31). The secretin PilQ from the T4PS of Neisseria meningitidis requires a lipoprotein chaperone, PilW, for multimer stability (3) and the Bam complex for correct assembly in the OM (45) and cannot assemble in vitro (20).…”
mentioning
confidence: 99%